Global Extension and Predominance of Human Metapneumovirus A2 Genotype with Partial G Gene Duplication - Muñoz-Escalante, Juan Carlos; Mata-Moreno, Gabriel; Rivera-Alfaro, Gerardo; Noyola, Daniel E. (Viruses, 2022)
Human metapneumovirus (HMPV) is an important respiratory pathogen and is divided in two main groups (A and B). HMPV strains with partial duplications (111-nt and 180-nt duplication) of the G gene have been reported in recent years. Since the initial reports, viruses with these characteristics have been reported in several countries. We analyzed all complete HMPV G gene ectodomain sequences available at GenBank to determine if viruses with 111-nt or 180-nt duplication have become the leading HMPV strains worldwide, and to describe their temporal and geographic distribution. We identified 1462 sequences that fulfilled study criteria (764 HMPV A and 698 HMPV B) reported from 37 countries. The most frequent HMPV A genotype was A2b2 (n = 366), and the most frequent B genotype was B2 (n = 374). A total of 84 sequences contained the 111-nt duplication, and 90 sequences contained the 180-nt duplication. Since 2016, viruses with a partial duplication comprise the most frequent HMPV A sequences globally and have displaced other HMPV A viruses in Asia, Europe, and South America; no sequences of viruses with partial duplication have been reported in North America or Africa so far. Continued surveillance of HMPV is required to identify the emergence and spread of epidemiologically relevant variants.